2023
DOI: 10.3389/fgene.2022.1056043
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiling in chronic lymphocytic leukaemia

Abstract: Background: DNA methylation aberrations are widespread among the malignant B lymphocytes of patients with chronic lymphocytic leukaemia (CLL), suggesting that DNA methylation might contribute to the pathogenesis of CLL.Aim: We aimed to explore the differentially methylated positions (DMPs) associated with CLL and screen the differentially methylated and expressed genes (DMEGs) by combining public databases. We aimed to observe the direction of each DMEG in CLL based on the DMPs in the promoter and the body reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…They found that ADAMTS17 was hypermethylated in the gene promoter region and hypomethylated in the gene body region. In contrast, FMOD and ZAP70 were hypomethylated in the promoter region ( 133 ). Regarding the involvement of B cells in SjS, abundant genes with differential DNA methylation in genetic at-risk loci ( HLA-DRA, HLA-DQB1 , IRF5 ) were observed ( 66 , 75 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that ADAMTS17 was hypermethylated in the gene promoter region and hypomethylated in the gene body region. In contrast, FMOD and ZAP70 were hypomethylated in the promoter region ( 133 ). Regarding the involvement of B cells in SjS, abundant genes with differential DNA methylation in genetic at-risk loci ( HLA-DRA, HLA-DQB1 , IRF5 ) were observed ( 66 , 75 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
“…It has been reviewed that aberrant expression of translational factors and modifications in the epigenetics in B cells is highly correlated with anomalous B cell functions in multiple diseases, including autoimmune diseases ( 132 ). For instance, analysis of differentially expressed and methylated genes shows the alterations of expression patterns and DNA methylation patterns of ADAMTS17 , FMOD , and Z AP70 in chronic lymphocytic leukemia (CLL) ( 133 ). They found that ADAMTS17 was hypermethylated in the gene promoter region and hypomethylated in the gene body region.…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
“…In total, 34,797 differentially methylated positions (DMPs) associated with the CLL genome were identified, most of which were hypomethylated and located in gene body regions. Among them, the methylation of ZAP70, FMOD, and ADAMTS17 was significantly different between CLL cases and controls [ 23 ]. Their roles in the pathogenesis of CLL deserve further exploration.…”
Section: Global Analysis Of Dna Methylation In Cllmentioning
confidence: 99%
“…Chromatin organization Methylation levels in specifc CpG sites independently predicted time to treatment [29] hTERT Chromosome maintenance signaling by WNT Promoter hypermethylation was associated with superior overall survival [30] CDKN2A/ 2B Capable of inducing cell cycle arrest in G1 and G2 phases and regulation of activated PAK-2 gene expression (transcription) Both genes' promoters have been found variously hypermethylated in CLL cases among diferent studies; common point of these studies was that hypermethylation of CDKN2A and CDKN2B was mutually exclusive in CLL cases [31][32][33][34] KLF4 G1-to-S transition of the cell cycle after DNA damage through p53 gene expression (transcription), NOTCH Aberrant methylation of the KLF4 promoter was signifcantly associated with gene expression levels compared to normal samples after B cell activation, KLF4 expression was reported to be downregulated [35] PTPN6 Cell growth, diferentiation, mitotic cycle, and oncogenic transformation In advanced Rai stage cases, aberrant methylation of PTPN6 promoter reached 70% in the samples examined [36] AGBL4 Metabolism of proteins actin and tubulin folding AGBL4 expression was reported to be reduced in patients with hypermethylated promoter regions and hypomethylated body regions [37,38] CLL: chronic lymphocytic leukemia, Ref. : reference, SMYD3: SE translocation and MYN-domain containing 3 protein, hTERT: human telomerase reverse transcriptase, CDKN2A/2B: cyclin-dependent kinase inhibitors 2A and 2B, KLF4: Krüppel-like factor 4, PTPN6: tyrosine-protein phosphatase nonreceptor type 6, AGBL4: ATP/GTP binding protein like 4, WNT: wingless-related integration site, PAK-2: P21 activated kinase 2, NOTCH: neurogenic locus notch homolog protein.…”
Section: Smyd3mentioning
confidence: 99%
“…: reference, SMYD3: SE translocation and MYN-domain containing 3 protein, hTERT: human telomerase reverse transcriptase, CDKN2A/2B: cyclin-dependent kinase inhibitors 2A and 2B, KLF4: Krüppel-like factor 4, PTPN6: tyrosine-protein phosphatase nonreceptor type 6, AGBL4: ATP/GTP binding protein like 4, WNT: wingless-related integration site, PAK-2: P21 activated kinase 2, NOTCH: neurogenic locus notch homolog protein. MGMT and hMLH1 DNA damage reversal homology-directed repair MGMT promoter region was rarely identifed to be hypermethylated, and hMLH1 promoter was reported to be hypermethylated in a small case series of indolent CLL with later Richter's transformation [32,[46][47][48][49][50] FHIT Loss of its activity results in replication stress and DNA damage In a limited series of CLL cases studied, FHIT promoter was reported to be hypermethylated [51][52][53] GSTP1 Important regulatory features in detoxifcation, antioxidative damage innate immune system GSTP1 promoter hypermethylation was reported in 2.7% of the samples controlled [51,[54][55][56] MACROD2 DNA damage response purine nucleoside metabolic process MACROD2 expression was demonstrated to be lower in cases with hypermethylated promoter regions and hypomethylated body regions [37,57] ADORA3 Activation of the NF-kB pathway, purinergic signaling, GPCR signaling Methylated gene body is reported in IGVH-mutated cases [26,58] CLL: chronic lymphocytic leukemia, Ref. : reference, RRM1: ribonucleotide reductase subunit 1, RRM2: ribonucleotide reductase subunit 2, RAD21: double-strand-break repair protein rad21, MGMT: methylguanine methyltransferase, hMLH1: human mutL homolog 1, FHIT: fragile histidine triad, GSTP1: glutathione S-transferase p1 gene, MACROD2: mono-ADP ribosylhydrolase 2, ADORA3: adenosine A3 receptor, NF-kB: Nuclear factor kappa B, GPCR: G protein-coupled receptor, LDH: lactic dehydrogenase, IGVH: immunoglobulin variable heavy chain gene.…”
Section: Smyd3mentioning
confidence: 99%